(untitled) (CIPEEX, 2025)
INTRODUCTION: Dyslipidemia, defined as abnormal levels of circulating lipids, is a major contributor to the development of cardiovascular diseases (CVDs), the leading cause of death globally. It may result from genetic predisposition or secondary causes such as poor dietary habits, sedentary lifestyle, and insulin resistance. Closely associated with atherosclerosis, dyslipidemia significantly increases the risk of myocardial infarction, stroke, and other cardiovascular events—particularly in individuals with metabolic dysfunction. Although early intervention through lifestyle modification is the first-line strategy for prevention and control, long-term adherence is often challenging. In this context, natural compounds such as berberine, a plant-derived isoquinoline alkaloid, have gained increasing attention due to their potential lipid-lowering, glucose-modulating, and insulin-sensitizing properties. However, clinical evidence remains limited and heterogeneous. OBJECTIVE: To analyze the effects of berberine in the management of metabolic disorders and its impact on early cardiovascular risk markers in adult populations. METHODS: An integrative literature review was conducted using the PubMed, LILACS, and MEDLINE databases. The search included studies published between 2018 and 2025 in English, Portuguese, or Spanish. Inclusion criteria comprised original clinical studies that evaluated the effects of berberine on cardiovascular risk factors in adults. Exclusion criteria included review articles, letters, dissertations, theses, and studies that did not respond directly to the research question. The descriptors used were “Berberine,” “Cholesterol,” and “Heart Disease Risk Factors” (DeCS/MeSH). After applying the eligibility criteria, five original studies were selected for final inclusion and analysis. RESULTS: The selected studies demonstrated a consistent association between berberine use and improvement in lipid profiles, with a mean reduction in total cholesterol of approximately 11% and LDL cholesterol of around 20%. No significant effect was observed on HDL cholesterol levels. Additionally, in studies involving nutraceutical formulations containing berberine, a notable increase in coronary flow reserve (CFR) was observed, an early marker of endothelial and coronary microvascular function. This suggests a dual benefit: lipid-lowering effects and improved vascular reactivity, both of which contribute to reduced cardiovascular risk. CONCLUSION: Berberine shows promise as an adjuvant therapy for managing metabolic disorders and mitigating cardiovascular risk in adults. It may offer a valuable alternative or complement for individuals with mild to moderate dyslipidemia, statin intolerance, or metabolic syndrome. Nevertheless, while short-term clinical trials report favorable outcomes, important knowledge gaps remain. These include the lack of long-term studies, standardized dosing, safety data over extended periods, and comparative trials versus conventional pharmacotherapies. Further high-quality research is necessary to establish berberine’s role in evidence-based cardiovascular prevention.